2015
DOI: 10.1371/journal.pone.0119045
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Changes across Different Clinical Milestones of Disease in Amyotrophic Lateral Sclerosis

Abstract: Neurodegenerative process in amyotrophic lateral sclerosis (ALS) has been proven to involve several cortical and subcortical brain regions within and beyond motor areas. However, how ALS pathology spreads progressively during disease evolution is still unknown. In this cross-sectional study we investigated 54 ALS patients, divided into 3 subsets according to the clinical stage, and 18 age and sex-matched healthy controls, by using tract-based spatial statistics (TBSS) diffusion tensor imaging (DTI) and voxel-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
38
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 76 publications
8
38
0
Order By: Relevance
“…Microstructural alterations in the CC found in our ALS population were similar to those reported in other cohorts of ALS patients [ 59 , 60 ]. Similar to previous studies, we performed a TBSS analysis of DTI data, a hypothesis-free technique which is capable of detecting structural changes over the whole brain and therefore highlights the structural process of disease spreading across WM fibers known to connect motor areas [ 59 , 60 , 63 ]. Structural neuroimaging evidence of CC damage seems to provide, in vivo , the same neuropathological signatures of neurodegeneration widely reported in both animal models [ 64 ] and autopsied patients [ 65 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Microstructural alterations in the CC found in our ALS population were similar to those reported in other cohorts of ALS patients [ 59 , 60 ]. Similar to previous studies, we performed a TBSS analysis of DTI data, a hypothesis-free technique which is capable of detecting structural changes over the whole brain and therefore highlights the structural process of disease spreading across WM fibers known to connect motor areas [ 59 , 60 , 63 ]. Structural neuroimaging evidence of CC damage seems to provide, in vivo , the same neuropathological signatures of neurodegeneration widely reported in both animal models [ 64 ] and autopsied patients [ 65 ].…”
Section: Discussionsupporting
confidence: 90%
“…A voxel-based TBSS approach was used for the group analysis of DTI data [ 38 ]. DTI data sets were processed with the Functional MRI of the Brain (FMRIB) Software Library (FSL) software package ( http://www.fmrib.ox.ac.uk/fsl ), according to methods used in our previous studies [ 59 , 60 ]. Preprocessing included eddy current and motion correction and brain-tissue extraction.…”
Section: Methodsmentioning
confidence: 99%
“…32 The hypothesis that ALSrelated pathology starts focally and progressively spreads through the anatomy of the motor system towards extramotor areas has been corroborated in several studies. 12,33,34 However, the region-specific alterations in PrCG has not yet been clearly elucidated. In this study, local atrophy of PrCG in ALS at a late stage was much more widespread than patients at an early stage, indicating that surface area atrophy starts locally and spreads to other areas in PrCG as time progresses.…”
Section: Discussionmentioning
confidence: 99%
“…Cross‐sectional DTI studies in ALS show widespread white matter changes in ALS subjects compared with healthy volunteers, and these changes correlate with upper motor neuron signs, ALSFRS‐R scores, verbal fluency, and the estimated rate of functional decline between the reported date of symptom onset and the date of scanning . Longitudinal DTI studies in ALS show more focal pathology, involving the corticospinal tract, corpus callosum, and posterior limb of the internal capsule in some studies, and other studies have shown more diffuse changes, including the cerebellum and the temporal and parietal lobes .…”
Section: Leading Candidatesmentioning
confidence: 95%